2018
DOI: 10.3233/rnn-170719
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in activities of daily living after visual training in patients with homonymous visual field defects using Goal Attainment Scaling

Abstract: Together these data suggest that (1) visual training aimed at vision restoration leads to visual field improvement and (2) the extent of visual field improvement is linearly related to the improvement of personal activities of daily living as evaluated by means of GAS. In conclusion, a personalized evaluation to assess treatment success showed the clinical significance of a visual training for vision restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…We found a relationship between objective visual improvements after training, as assessed by Goldmann perimetry and the GAS scores. Furthermore, for the Humphrey perimetry, we found a linear relationship only between GAS scores and the directed training effects for the full visual field (Elshout et al, 2018). These findings emphasise the value of our quantification of the change in visual field sensitivity, i.e.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We found a relationship between objective visual improvements after training, as assessed by Goldmann perimetry and the GAS scores. Furthermore, for the Humphrey perimetry, we found a linear relationship only between GAS scores and the directed training effects for the full visual field (Elshout et al, 2018). These findings emphasise the value of our quantification of the change in visual field sensitivity, i.e.…”
Section: Discussionsupporting
confidence: 54%
“…A substantial number of studies have reported functional improvements within the VFD measured using either ophthalmic, electrophysiological or psychophysical tests (Bergsma et al, 2012;Bergsma and Van Der Wildt, 2010;Bergsma et al, 2017;Elshout et al, 2018;Elshout et al, 2016;Huxlin and Cavanaugh, 2017;Julkunen et al, 2003;Kasten et al, 1998;Marshall et al, 2010;Mueller et al, 2007;Romano et al, 2008;Sahraie et al, 2006;Jobke et al, 2009) or neuroimaging (Julkunen et al, 2006;Marshall et al, 2010;Raemaekers et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning vision, an improvement in visual acuity was observed between T0 and T1, as well as increased contrast sensitivity and wider visual field as documented by the GAS 41 which highlights an improvement at T1 that affects significantly the activities of daily living (ADL) (see Table 3). Compared to baseline (2/10 for distance, 6 DW for near), the patient achieved a visual acuity of 3/10 for distance and fluctuated between 3 DW and 1 DW for near vision when she was better able to control nystagmus.…”
Section: Visual Functions Assessmentmentioning
confidence: 86%
“…Visual functions assessment was performed with a standard visual acuity test, Goldman kinetic perimetry, 40 and Goal Attainment Scale (GAS). 41 GAS is a sensitive individualized, criterion-referenced method measuring specific outcomes on individual goals after a period of treatment and widely used to supplement standardized measures of outcome that investigated, pre/post treatment and in follow-up, the modification of specific parameters; in our article, we have analyzed compliance with the treatment, visual acuity, visual field, and visual fixation. The assessment of dysarthria was performed by means of dysarthria profile.…”
Section: Methodsmentioning
confidence: 99%
“…In order to relate perimetry results with personal improvement in daily life activities, GAS was applied by three independent occupational therapists, who were blinded to training outcome. A more detailed description about how GAS was applied can be found in 20. In brief, each patient sets three SMART (Specific, Measurable, Achievable, Realistic, Time orientated) goals prior to training under supervision of the therapist 19.…”
Section: Goal Attainment Scalingmentioning
confidence: 99%